EXTENT OF ADOPTION OF STRATEGIC MANAGEMENT ACCOUNTING PRACTICES IN SELECTED NIGERIAN CONSUMER GOODS COMPANIES - Grace Olayemi AJAYI; Yemisi OLABISI-AYODELE; Olukayode OYEDEJI (Malete Journal of Accounting and Finance, 2023)
The place of Strategic Management Accounting (SMA) in contemporary business organizations cannot be over-emphasized. Research has shown that organizations that employ the tools of SMA tend to remain competitive in their industry of operation. Therefore, this study examines the adoption of Strategic Management Accounting Practice in selected Nigerian Consumer Goods Companies with a view to establishing the extent of the adoption of this practice. The study made use of primary data obtained from structured questionnaires administered to concerned managers of the companies. Purposive sampling technique was used to obtain a sample size of 18 firms because of the technicality of the subject matter as well as the availability of required respondents. The data generated was analyzed using descriptive statistics. It was found that all 21 SMA practices examined were adopted with Benchmarking having the highest mean statistics of 4.73 and theory of constraint is the least adopted with an average of 3.36. The study concludes that there is a high rate of adoption of the SMA practices and consequently recommends that the others like theory of constraint and kaizen costing that have relatively lower rate of adoption should be considered by companies that are yet to.